DE ECHAVE, José; Alejandro DIEZ; Ludwig HUBER; Bruno REVESZ; Xavier RICARD LANATA y Martín TANAKA. Minería y conflicto social. Lima: CBC, CIPCA, CIES, IEP, 2009.424 pp. - Barrio de Mendoza, Rafael (2010)
No presenta resumen